Does a self-referral counselling program reach doctors in need of help? A comparison with the general Norwegian doctor workforce - Gude Tore; Rø Karin; Aasland Olaf G (BMC, 2007)
Abstract Background Doctors have a relatively high degree of emotional distress, but seek help to a lesser degree and at a later stage than other academic groups. This can be deleterious for themselves and for their patients. Prevention programs have therefore been developed but it is unclear to what extent they reach doctors in need of help. This study describes doctors who participated in a self-referrral, easily accessible, stress relieving, counselling program in Norway, and compares them with a nationwide sample of Norwegian doctors. Methods Two hundred and twenty seven (94%) of the doctors, 117 women and 110 men, who came to the resort centre Villa Sana, Modum, Norway, between August 2003 and July 2005, agreed to participate in the study. Socio-demographic data, reasons for and ways of help-seeking, sick-leave, symptoms of depression and anxiety, job stress and burnout were assessed by self-reporting questionnaires. Results Forty-nine percent of the Sana doctors were emotionally exhausted (Maslach) compared with 25% of all Norwegian doctors. However, they did not differ on empathy and working capacity, the other two dimensions in Maslach's burnout inventory. Seventy-three percent of the Sana doctors could be in need of treatment for depression or anxiety based on their symptom distress scores, compared with 14% of men and 18% of women doctors in Norway. Twenty-one percent of the Sana doctors had a history of suicidal thoughts, including how to commit the act, as compared to 10% of Norwegian doctors in general. Conclusion Sana doctors displayed a higher degree of emotional exhaustion, symptoms of depression and anxiety as well as job related stress, compared with all Norwegian doctors. This may indicate that the program at Villa Sana to a large extent reaches doctors in need of help. The counselling intervention can help doctors to evaluate their professional and private situation, and, when necessary, enhance motivation for seeking adequate treatment.